Pengembangan bahan ajar digital berbasis STEM (Science, Technology, Engineering, and Mathematic) pada sub materi mitigasi bencana alam di Indonesia - Indana Zulfiya; Sumarmi Sumarmi; Satti Wagistina; Fatiya Rosyida (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2023)
Teaching materials are essential in teaching and learning activities that help students achieve learning goals. STEM-based teaching materials can support geography learning, encouraging students to solve problems actively, creatively, and innovatively because they use various scientific perspectives. The aim of this research is to produce STEM (science, technology, engineering, and mathematics)-based digital teaching material development products in the sub-material natural disaster mitigation in Indonesia. The development research model uses the ADDIE procedure and is limited to the development stage, which focuses on making product development. The quality of teaching materials is measured by the level of validity and feasibility when used in learning. Based on the results of the assessment by experts, it proves that digital teaching materials are very valid for use in learning. The feasibility test that has been carried out on geography teachers and 32 class XII students at MAN Batu City states that the development product is very feasible to use. Based on the results of this study it can be concluded that STEM-based digital teaching materials with a high level of feasibility can be used for learning Geography. Bahan ajar adalah komponen penting dalam kegiatan belajar mengajar yang membantu siswa mencapai tujuan pembelajaran. Bahan ajar berbasis STEM dapat menunjang pembelajaran geografi yang mampu mendorong siswa untuk menyelesaikan permasalahan dengan aktif, kreatif, dan inovatif dikarenakan menggunakan berbagai sudut pandang keilmuan. Tujuan dalam penelitian ini adalah menghasilkan produk pengembangan bahan ajar digital berbasis STEM (science, technology, engineering, and mathematic) pada sub materi mitigasi bencana alam di Indonesia. Model penelitian pengembangan menggunakan prosedur ADDIE dan dibatasi sampai tahap development yang fokus pada pembuatan produk pengembangan. Kualitas bahan ajar diukur dari tingkat validitas dan kelayakan jika digunakan dalam pembelajaran. Berdasarkan hasil penilaian oleh ahli membuktikan bahwa bahan ajar digital sangat valid untuk digunakan dalam pembelajaran. Uji kelayakan yang telah dilakukan pada guru geografi dan 32 siswa kelas XII di MAN Kota Batu menyatakan bahwa produk pengembangan sangat layak untuk digunakan. Berdasarkan hasil kajian tersebut dapat diambil kesimpulan bahwa bahan ajar digital berbasis STEM dengan tingkat kelayakan yang tinggi dapat digunakan untuk pembelajaran Geografi.